1989
DOI: 10.1159/000110171
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in a French Prospective Population Study

Abstract: Since 1985 there has been a Stroke Registry in Dijon to record every stroke occurring in the population of a city of 140,000 inhabitants. The survey has been exhaustive and included the numerous sources of information as well as CT scanning. The annual incidence is 145/100,000 with an annual specific incidence of 170/100,000 in men, 126/100,000 in women. The annual specific incidence shows a female preponderance until 30 years of age, after which the males lead from the age of 30 to 80, when the rates become e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
35
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 4 publications
11
35
1
2
Order By: Relevance
“…However, the proportion of subarachnoid hemorrhage in the present study was lower than in other previous studies in Japan (10,16,17,22) and almost similar to those in the United States and in France (19,23). Some previous studies showed that more than 75% of subarachnoid hemorrhage cases occurred in the age group under 60 years old (24,25).…”
Section: Seasonal Variationssupporting
confidence: 51%
See 1 more Smart Citation
“…However, the proportion of subarachnoid hemorrhage in the present study was lower than in other previous studies in Japan (10,16,17,22) and almost similar to those in the United States and in France (19,23). Some previous studies showed that more than 75% of subarachnoid hemorrhage cases occurred in the age group under 60 years old (24,25).…”
Section: Seasonal Variationssupporting
confidence: 51%
“…Some people may suggest that the high proportion of cerebral hemorrhage and high rate of performing CT in the present study reflects the poor identification of cerebral infarction with mild symptoms. However, this suspicion is off the point because the case-fatality rate within 30 days after onset was not high but rather low in comparison with previous studies (18)(19)(20) and case ascertainment was estimated to be almost complete. Poor management of hypertension may be one of the reasons for the high proportion of cerebral hemorrhage in Okinawa.…”
Section: Seasonal Variationsmentioning
confidence: 69%
“…The higher stroke incidence in males could be explained by data from the Brazilian Ministry of Health, which showed a higher prevalence of risk factors for stroke among males in 15 Brazilian state capitals, including the state where Matão city is located. 30 The 30-day and 1-year case fatality rates were among the lowest reported in the literature, [21][22][23][25][26][27][28]31,32 only exceeding those observed in Scotland 24 and in Rochester. 33 This fact could be explained by the high proportion of lacunar infarcts, which have also shown a low mortality in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…Whereas only 6.0% of the Brazilian population is older than 65 years, in other studies this percentage ranges from 13.1% to 21%. [21][22][23][24][25][26][27] The fact that stroke is a disease that mainly affects elderly people can be one reason explaining the low overall crude incidence rate of 108 per 100 000 persons when compared with other series. A low overall crude incidence rate of 73.6 per 100 000 was also observed in a populationbased study performed in Iquique, Chile, 28 a South American country with a socioeconomic level similar to that of Brazil and with 5.5% inhabitants older than 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have demonstrated that the incidence of stroke increases in the winter and spring and decreases in the summer and autumn. [3][4][5][6][7][8][9][10][11] However, some studies have reported increases in the incidence of stroke in response to dramatic temperature changes in the spring and autumn, [12][13][14] whereas in other studies, no seasonal variation has been demonstrated. [15][16][17] Because most previous studies have addressed large regions with varying climate, studies on smaller regions with similar weather and environments could provide important information on this topic.…”
mentioning
confidence: 99%